Kepemimpinan Partisipatif dan Komunikasi Kepala Sekolah terhadap Kinerja Guru - Armi Yuneti; Hamdan Hamdan; Ahmad Gawdy Prananosa (Journal Of Administration and Educational Management (ALIGNMENT), 2019)
The purpose of this study was to determine the effect of participatory leadership and school principal communication on teacher performance. This research uses a quantitative approach with multiple regression methods. The results of the study, through regression calculations, obtained the calculated F price of 9,246 while the F price of 5% table in db (53-2) was 4.11 and the F price of 1% table in db (53-2) was 7.35. So the relationship between participative leadership and principal communication together with teacher performance, is significant. In conclusion, there is an influence of participatory leadership and school principal communication with teacher performance. Keywords: Participatory Leadership, Communication, Teacher Performance